Epithelial–Mesenchymal Transition in Cancer Progression: Biological Basis and Histopathological Implications - Gestin, Dustia; Oktavia, Ria (Frontiers on Healthcare Research, 2026)
Background: Epithelial–mesenchymal transition (EMT) is a fundamental biologic process that plays a critical role in tumor invasion, metastasis, and dedifferentiation. While extensively investigated in molecular oncology, its relevance to routine surgical pathology practice remains underemphasized. Many morphologic alterations observed in daily histopathologic evaluation represent phenotypic manifestations of EMT, yet these findings are often interpreted descriptively without integration into a unified biologic framework. Methods: This review aims to provide a practical overview of EMT from a surgical pathology perspective by correlating biologic mechanisms with histomorphologic features, immunohistochemical findings, and clinical implications across solid tumors.A narrative literature review was conducted using PubMed/MEDLINE databases to identify relevant studies published between 2020 and 2025. Keywords related to EMT, histopathology, tumor progression, and immunohistochemistry were applied. Selected articles were qualitatively synthesized with emphasis on clinicopathologic relevance and applicability to routine diagnostic practice. Results: EMT is characterized by loss of epithelial differentiation, acquisition of mesenchymal traits, and increased cellular plasticity. Histologically, EMT correlates with recognizable features including loss of cellular cohesion, tumor budding, single-cell invasion, spindle cell transformation, and tumor dedifferentiation. Immunohistochemical alterations such as decreased E-cadherin expression and increased mesenchymal marker expression further support EMT-associated phenotypes. Across multiple organ systems, these morphologic changes are consistently associated with aggressive tumor behavior, metastatic potential, and therapeutic resistance. Conclusion: EMT provides a unifying concept linking molecular cancer biology with routine histopathologic observations. Recognition of EMT-associated morphologic patterns may enhance prognostic assessment and strengthen clinicopathologic interpretation, reinforcing the essential role of histopathology in the era of precision oncology.